1988
DOI: 10.1111/j.1469-7998.1988.tb04993.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial albinism and natural selection in the hooded crow Corvus corone cornix

Abstract: We studied the frequency of partial albinism amongst hooded crows in Norway, mostly in a population at Trondheim. A total of 3461 birds were collected from the field. About 5% of fledged young showed albinoid markings on their third right‐hand primary; the frequency decreased to 2% among yearling birds and to only 1% among birds that had acquired their adult plumage. No significant difference was found in relation to sex. The partially albinoid birds were typically small‐sized, both as regards their bone struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…In a study of hooded crows Corvus corone cornix, Slagsvold et al (SLAGSVOLD et al 1988) found that albinistic individuals were on average smaller than individuals of normal plumage coloration. Partially albinistic barn swallows Hirundo rustica have been found to exhibit lower between year survival than normally coloured individuals (ELLEGREN et al 1997).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study of hooded crows Corvus corone cornix, Slagsvold et al (SLAGSVOLD et al 1988) found that albinistic individuals were on average smaller than individuals of normal plumage coloration. Partially albinistic barn swallows Hirundo rustica have been found to exhibit lower between year survival than normally coloured individuals (ELLEGREN et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Hence, by monitoring partial albinism in long term or geographically large scale studies, we might be able to identify populations exposed either to inbreeding or environmental stress. An advantage with the use of partial albinism as a stress indicator is that museum collections can be used as reference populations (SLAGSVOLD et al 1988;ELLEGREN et al 1997) to establish whether the observed level of albinism is atypical relative older samples or samples from other geographical regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological abnormalities are therefore infrequent in natural populations. Current evidence for the action of natural selection on morphological abnormalities is often indirect 5 , 6 in part because of the difficulty in obtaining large samples of rare phenotypic traits. Consequently, empirical data to test theoretical predictions and measure the magnitude and direction of predicted effects are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, in this article, the term ‘leucism’ (from the Greek leukos , ‘white’) should be interpreted according to its original and all-embracing meaning, as denoting the absence of melanin in the integument, regardless of the underlying process 7 . Lastly, non-genetic (environmental) factors, such as injury 17 and nutritional constraints on melanization 5 may also cause loss of pigmentation. Many questions remain about the causes and biological significance of leucism, yet the relative ease of detection of this trait can facilitate data collection and provide useful information to understand the emergence and maintenance of colour aberrations in natural populations 18 .…”
Section: Introductionmentioning
confidence: 99%